Combined bio-chemical fertilizers ameliorate agro-biochemical attributes of black cumin (Nigella sativa L.) - Samira Moradzadeh (Nature Portfolio, 2021)
Abstract Nigella sativa L. is a medicinal plant with extensive, nutritional, pharmaceutical, and health applications. Nowadays, reducing the application of chemical fertilizers (synthetic fertilizers) is one of the main goals of sustainable agriculture to allow the production of safe crops. Therefore, the combined effect of urea and biofertilizers was studied on the quantitative and qualitative traits of N. sativa L. in a randomized complete block design with 10 treatments and three replications. The treatments included control (no fertilization), U (100% chemical fertilizer as urea at 53.3 kg ha−1, Nb (Biofertilizer, Azotobacter vinelandii), Pb (Biofertilizer, Pantoea agglomerans and Pseudomonas putida), Kb (Biofertilizer, Bacillus spp.), NPKb (NPK, biofertilizer), Nb + 50% U, Pb + 50% U, Kb + 50%U and NPKb + 50% U. The NPK(b) + U50% was related to the highest quantity of plant height, branch diameter, capsule (follicle) number per plant, auxiliary branches, seed yield per plant, thousand-seed weight, essential oil content, total phenolic compounds, flavonoid content, DPPH free radical scavenging, nitric oxide (NO) radical scavenging, superoxide radical scavenging, chain-breaking activity, phosphorus content, and potassium content, along with U for the highest biological yield and (Pb) + U50% for the highest essential oil percentage which is close to (NPKb) + U50%. The lowest value was observed in all traits related to the control treatment except for branch diameter that was related to (NPKb). Hence, the application of (NPKb) + U50% as bio-chemical fertilizers improved N. sativa L. Traits, so it can be recommended.